Changes in cerebral haemodynamics in patients depending on the severity and catamnesis of combat traumatic brain injury - Chernenko, I. (Journal of Education, Health and Sport, 2025)
In our time, under the influence of the ATO in the East of Ukraine and the full-scale invasion of Ukraine by the Russian Federation, the incidence of combat injuries, particularly combat traumatic brain injuries (cTBI), has significantly increased. The traumatic factor initiates a series of pathological processes, including immune, hemodynamic, metabolic, etc. These processes further shape the long-term consequences of cTBI. The cerebral vascular system is highly sensitive to mechanical impacts. Over time, vascular processes become more aggressive, and cerebrovascular accidents that develop often have a pessimistic prognosis. Purpose. To determine the peculiarities of changes in cerebral hemodynamics in patients with cTBI depending on the severity and duration of the condition and to correlate these changes with clinical manifestations. Materials and Methods. The study involved 350 male patients with cTBI, conducted at the Municipal Non-Profit Enterprise of the Kharkiv Regional Council "Regional Hospital for War Invalids." Patients were divided into groups based on the severity of their injury: 145 individuals with mild cTBI (mTBI), 125 with moderate cTBI(MT), and 80 with severe cTBI (sTBI). The duration of the condition (catamnesis) was also considered: from 6 months to 1 year, 1 to 3 years, and 4 to 7 years. The average age of the patients was 38.5 ± 1.5 years. A control group consisted of 30 relatively healthy individuals matched by sex and age, without a history of cTBI. Neurological status and primary syndromes were studied, along with laboratory and instrumental methods, including ultrasound dopplerography of the head and neck vessels (USDG). The study utilized the Versana Essential diagnostic ultrasound system, employing a linear transducer L6-12-RS with a frequency range of 4.0–13.0 MHz. Results and Discussion. Measurements of the intima-media thickness of the carotid artery (IMT) were conducted. In the mTBI and TBI(MT) groups, mean IMT values were within normal ranges (0.78 mm and 0.8 mm, respectively). However, in the sTBI group, there was an increase of approximately 15.0%. In the mTBI group, normal Doppler signal spectra corresponding to the relevant arteries were observed. No pathological turbulence was detected. Interhemispheric asymmetry in the carotid basin was within acceptable limits. In contrast, the TBI(MT) and sTBI groups exhibited reduced curve amplitude, elevated incisura, and the absence of a "systolic window." Changes in the vertebrobasilar basin (VBB) included a decrease in blood flow velocity by 26.5%, an increase in pulsatility index (PI) by 42.6%, and an increase in resistance index (RI) by 22.5%. These changes were accompanied by significant decreases in blood flow in the middle cerebral artery (MCA). Conclusions. Changes in cerebral hemodynamics are closely correlated with the severity of cTBI and the duration of the condition. The longer the time since the injury, the more pronounced the progressive deterioration in cerebral blood flow due to the exhaustion of vascular tone regulation mechanisms. In the sTBI group, there was a significant decrease in velocity characteristics and an increase in PI, RI, and resistance coefficients in both the carotid and vertebrobasilar basins. This emphasizes the need for continuous monitoring of patients with sTBI due to the high risk of vascular complications